Physical Activity in People with Intellectual Disability: A Narrative Review - Javid Mostamand; Hamzeh Baharlouei (Vesnu Publications, 2019)
Introduction: The levels of physical activity and exercise are two important factors to improve health in people with intellectual disability. Several studies addressed the level of physical activity, and the benefits, cautions, and principles of exercising in this group of disabled people. The aim of the current study was to review the articles related to both topics of intellectual disability and exercise to provide a suitable framework for improving physical activity in people with intellectual disability. Materials and Methods: Databases including PubMed, PEDro, Science Direct, and Magiran were considered to search, using the keywords physical activity, exercise, intellectual disability, and Down's syndrome to find related articles. Finally, twenty two studies which met the inclusion criteria were selected, and the related data including the level of physical activity, and the benefits and principle of exercise prescription were extracted. Results: Despite approved benefits of physical activity, the level of exercise in people with intellectual disability was lower than other peer groups. In people with intellectual disability, especially people with Down's syndrome, medical conditions such as cardiovascular, physical, mental, and health disorders should be assessed before prescription of any exercises. Aerobic, resistance, and balance training are the most important exercises in people with intellectual disability. Conclusion: Exercise has a pivotal role for improving health in people with intellectual disability. These people have to pass some medical examinations before prescription of any exercise program.